Computers and Games 6th International Conference, CG 2008 Beijing, China, September 29 - October 1, 2008. Proceedings - van den Herik, H. Jaap; Xu, Xinhe; Ma, Zongmin; Winands, Mark H.M (Theoretical Computer Science and General Issues,, 2008)
This book constitutes the refereed proceedings of the 6th International Conference on Computers and Games, CG 2008, held in Beijing, China, in September/October 2008 co-located with the 13th Computer Olympiad and the 16th World Computer-Chess Championship. The 24 revised full papers presented were carefully reviewed and selected from 40 submissions. The papers cover all aspects of artificial intelligence in computer-game playing dealing with many different research topics, such as cognition, combinatorial game theory, search, knowledge representation, and optimization.